Problems in the formation and implementation of the methodology for investigating homicides related to domestic violence (Law and Safety, 2023)
The theoretical foundations for building a separate forensic methodology for investigating homicides committed in connection with domestic violence have been developed. A scientific justification for the differentiation of the relevant type of homicide in the system of forensic classification of criminal offences related to domestic violence has been proposed. Certain elements of the methodology for investigating this type of homicide and their specificity in the context of developing forensic recommendations have been identified. Characteristics of the practical implementation of the methodology for investigating homicides committed in connection with domestic violence have been provided. A systematic analysis of the elements of the mechanism of domestic homicide and domestic violence, the activities of law enforcement agencies to prevent, detect and investigate this type of homicide, as well as scientific recommendations concerning the methodological and forensic support of pre-trial investigation in criminal proceedings on homicide has been carried out. Legislation regulating social relations in the field of domestic violence prevention, as well as judicial and investigative practice in criminal proceedings on homicide related to domestic violence have been studied. On this basis, it has been determined that homicide committed in connection with domestic violence is a type of domestic (household) homicide, the investigation process of which is characterised by specific features which necessitate the formation of a corresponding separate subspecies forensic methodology. The main distinguishing feature of this homicide group is predicate domestic violence, i.e. violence that systematically occurs in the family before the actual event of the homicide. An important reason for differentiating the methodology of investigating such homicides is the forensic classification of domestic violence as a separate phenomenon and criminal offences related to it. These classifications also make it possible to detail individual elements of the methodology for investigating the category of homicide under study, including typical investigative situations, versions, tactical tasks of the investigation, algorithms of investigator's actions and tactical operations. A specific aspect of the formation and practical implementation of the methodology for investigating homicides committed in connection with domestic violence is to take into account the peculiarities of the behaviour and psychology of the offender, the victim and, in some cases, witnesses of domestic violence when choosing means of evidence (investigative actions) and tactics for their conduct. This significantly affects the specification of typical investigative situations of the initial and subsequent stages of the investigation, as well as determines the specific tactics of certain procedural actions, including inspection of the scene, interrogation, involvement of experts, etc.
Keywords: forensic methodology; homicide investigation; investigation of domestic homicide; investigation of domestic violence; criminal proceedings; forensic characteristics; investigative situations; investigation planning; tactics of investigative (detective) actions.